PENGARUH STRATEGI DIVERSIFIKASI TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2015-2019) - Tri Nurhayati; Risal Rinofah (ITB AAS Indonesia Surakarta, 2021)
The purpose of this study was to determine the effect of diversification strategies on company financial performance with profitability as an intervening variable. This research was conducted at manufacturing sector companies listed on the Indonesia Stock Exchange 2015-2019. The type of data used is secondary data, while the sample selection method uses purposive sampling, obtained 40 sample companies. The analysis technique used is path analysis using the SPSS application program. The results of this study indicate that the diversification strategy has a positive effect on the company's financial performance, and profitability mediates the effect of the diversification strategy on the company's financial performance. Keywords : Diversification Strategy; Profitability; Corporate’s Financial Performance